Implementation of Law Number 8 of 1999 on Consumer Protection in Online Buying and Selling Practices: A Maqashid Shariah Perspective - Nilfatri , Nilfatri; Syukri, Ahmad; Ramlah, Ramlah (Journal of Law, Politic and Humanities, 2025)
Abstract: This study examines the implementation of Law Number 8 of 1999 concerning Consumer Protection (UUPK) in online buying and selling (e-commerce) practices from a Maqashid Shariah perspective. The background of the study arises from the rapid development of digital transactions that have brought challenges to consumer protection, such as online fraud, product discrepancies, delivery delays, and misuse of personal data. This study used a qualitative descriptive approach with an empirical juridical method, involved interviews with the Department of Industry and Trade of Jambi Province and the Indonesian Consumers Foundation (YLKI) of Jambi Province, and was complemented by a literature review. The results of the study show that the principles of consumer protection in the Consumer Protection Law (UUPK) show substantial alignment with the objectives of Maqashid Syariah, particularly in preserving property (hifz al-mal), life (hifz al-nafs), and dignity (hifz al-‘ird). However, the UUPK still has weaknesses in responding to the characteristics of digital transactions, including the absence of specific regulations on electronic commerce, weak law enforcement based on digital evidence, limitations in the function of Consumer Dispute Settlement Agency (BPSK), the lack of regulation on personal data protection, the minimal obligation of transparency for online business actors, and the insufficient adaptability to new digital business models. This study recommends revising the Consumer Protection Law (UUPK) to be more responsive to technological developments, strengthening consumer dispute settlement institutions, synchronizing regulations, and enhancing public legal literacy based on the principles of justice and welfare according to Maqashid Syariah. (time new roman, size 12, space 1)enter 1 xKeyword: Consumer protection, Online trading, Consumer protection law (UUPK), Maqashid syariah, E-commerce.